A Proof of Concept of the Contribution of Tele-auscultation in the Screening of Heart Disease: A Cross Sectional Study - Goethe Doualla, Fred-Cyrille; Bediang, Georges; Nganou-Gnindjio , Chris; Boombhi , Jerome; Kingue, Samuel (Journal of Health Informatics in Africa, 2021)
Background and purpose: Cardiovascular diseases are the leading cause of death worldwide, accounting for 31% of all deaths in 2016. Echocardiography is the reference screening tool, but its widespread use in developing countries is limited by its high cost. The objective of this study was to evaluate auscultation of heart sounds using an electronic stethoscope coupled with tele-transmission and remote interpretation by a distant physician as a less expensive alternative. Methods: This was a descriptive cross-sectional study. Participants meeting inclusion criteria were examined face-to-face by a cardiologist (A) using a traditional stethoscope and following a well-defined protocol. Heart sounds were then recorded by a health professional using an electronic stethoscope. A part of these digital auscultation records were randomly selected and evaluated by cardiologist (A) and remotely (via a telemedicine platform) by cardiologist (B), then rated as normal or abnormal. Diagnostic findings of cardiologists A (digital-based) and cardiologist B (remote) were compared to those found by the cardiologist (A) during face-to-face consultation by using the Cohen?s Kappa coefficient. Results: We enrolled 22 patients in the study and ten (n=10) were randomly selected for analysis. The level of agreement between face-to-face and digital-based auscultatory findings by cardiologist A was moderate (K = 0.583). It was satisfactory (K= 0.615) between face-to-face auscultatory findings by cardiologist A and tele-auscultation findings by cardiologist B. Conclusions: This study highlights the potential of using a tele-auscultation system in the assessment of cardiovascular diseases in remote areas (developing countries) where there is a shortage of qualified personnel. Keywords: Telemedicine, Tele-auscultation, Screening, Heart disease, Electronic stethoscope